Surface-mediated targeting of lentiviral vectors - Buchholz, Christian (Henry Stewart Talks, 2014)
In vivo and ex vivo gene therapy, Cell entry modes of retroviral vectors, Molecular functions of viral envelope proteins, Introduction to surface targeting, Targeting subtypes of lymphocytes and hematopoietic stem cells (Ex vivo), In vivo targeting (local vs. systemic administration)